Synthesis of Linear Enamides and Enecarbamates via Photoredox Acceptorless Dehydrogenation. Issue 4 (31st January 2023) - Ritu,; Kolb, Daniel; Jain, Nidhi; König, Burkhard
Abstract: In recent years, several methods for the direct desaturation of aliphatic compounds have been developed, facilitated by the unique combination of photoredox and transition‐metal catalysis. Hereby, alkenes with high functionalization potential can be prepared in a straightforward fashion. We adapted a previously reported system involving tetrabutylammonium decatungstate (TBADT) as hydrogen atom transfer (HAT) agent and a cobaloxime co‐catalyst for dihydrogen evolution for the dehydrogenative preparation of linear enamides and enecarbamates from saturated precursors. The substrate scope includes several natural products and drug derivatives. The reaction does not require noble metal catalysts, exhibits short reaction times compared to previous methods and is suitable for the late‐stage functionalization of drug derivatives. Abstract :